(untitled) (GYMNASIUM, 2011)
The structure of the education system in our country, physical education and sport are integrated into their content teaching school, achievement in full harmony, both the optimal level of development and physical training and learning and practicing different sports to leisure in a useful, entertaining and enjoyable.